Faktor Penyebab Rendahnya Penguasaan Operasi Perkalian Pada Peserta Didik Kelas IV SD - Ivone Sinolidi; Khairunnisa Khairunnisa; Firdan Sulistiana; Ricky Raisandi; Adit Adit (JURNAL DIKDAS, 2026)
This This descriptive qualitative research aims to analyze the obstacles in mastering multiplication operations among fourth-grade students at SD Inpres Bumi Sagu through observation, interviews, basic ability tests, and documentation. The results reveal that the students' low proficiency is caused by a combination of internal and external factors. Internally, students experience misconceptions where multiplication is perceived merely as rote memorization, accompanied by low abstract thinking skills, a lack of motivation, and low self-confidence. Externally, obstacles arise from conventional and monotonous teaching methods with minimal use of concrete media, as well as a lack of parental guidance at home. As a solution, it is necessary to implement innovative learning strategies such as the jarimatika method and the use of engaging visual media. Furthermore, providing motivation through games before learning and increasing the synergy between teachers and parents are crucial to creating a conducive learning environment so that students' understanding of multiplication concepts can increase significantly.